MANIFESTATIONS OF PATHOMORPHOLOGICAL CHANGES IN RETINAL LAYERS AFTER TEN WEEKS OF OPIOID EXPOSURE IN THE EXPERIMENT - Paltov, Ye.V.; Kovalishin, O.A.; Fik, V.B.; Krivko, Yu.Ya.; Pankevych, L.V. (World of Medicine and Biology, 2018)
The present work was aimed to study the appearance and manifestations of pathomorphological angio- and neuroretinopathy against the background of chronic effects of therapeutic doses of opioid analgesics. The purpose was achieved using the histological method of visualization of the retina. Histologic preparations were prepared according to the generally accepted method with the use of dye hematoxylin, eosin, and (azan) according to the method of Heidenghain. The results of the study in the future will allow the formation of a pathomorphological basis that can be used to perform a comparative characterization of the retina layers and its microcirculatory bloodstream in norm with the data of the experimental opioid effects and the correction results. As a result of our microscopic study of the rat retinal layers structural organization, after ten weeks of the experiment, the pigment epitheliocyte cytoplasm (I) is enlightened, containing vacuoles. In separate areas of the retina, the nucleus of the pigmented epithelium is fissured (caryolysis), the cytoplasm splits into separate fragments or mesh mass (plasmorexis), and in separate cells the cytoplasm is molten. In the groups of photosensory cells (II) enlightenment was revealed, with the formation of microcystous cavities. In such areas, nuclei of photosensory cells are moving. In the external boundary layer (III), no signs of pathology were detected at this stage of the experiment. In the outer nuclear layer (IV), the amount of wrinkled nuclei of irregular shape grows. The number of nuclei rows of the retina outer nuclear layer in the area of the optic nerve disc changes amounting to 4-8. It should be noted that necrotic changes in the photoreceptor nuclei are accompanied by changes in their axons and external areas of photosensory cells, which is manifested by the formation of microscopic cavities in the outer plexiform layer and destruction, shortening of the outer regions of photoreceptors, and sometimes by the dissection of photoreceptors’ internal areas. The displaced nuclei of amakrine cells, as well as lymphocytes, were detected in the inner retinal layer (VII). In the ganglionic layer (VIII) there are areas in which the ganglionic cells do not form a continuous layer, located rather apart from each other. Some nuclei of irregular shape, wrinkled (karaopicnose), when stained with azan, become intensely red. The cytoplasm in these cells is irregularly colored, is collected in separate clumps. At the nerve-fiber layer’s boundary there are sometimes microscopic cavities. The ten-week experimental opioid effect causes vacuolar dystrophy and necrotic changes in the pigment epithelium, destruction of photosensory cells, microcystic degeneration of the outer retinal layer, focal necrotic changes of ganglion cells and cells of the inner nuclear layer, and the restructuring of the retinal hemomicrocirculatory bed. The above will further provide an opportunity to develop methods for optimal correction of angio- and neurotrophic retinopathy that have arisen as a result of opioid exposure.